Effect of multi-walled carbon nanotube surface modification on bioactivity in the C57BL/6 mouse model. Issue 3 (May 2014) - Sager, Tina M.; Wolfarth, Michael W.; Andrew, Michael; Hubbs, Ann; Friend, Sherri; Chen, Teh-hsun; Porter, Dale W.; Wu, Nianqiang; Yang, Feng; Hamilton, Raymond F.; Holian, Andrij
Abstract The current study tests the hypothesis that multi-walled carbon nanotubes (MWCNT) with different surface chemistries exhibit different bioactivity profiles in vivo. In addition, the study examined the potential contribution of the NLRP3 inflammasome in MWCNT-induced lung pathology. Unmodified (BMWCNT) and MWCNT that were surface functionalised with -COOH (FMWCNT), were instilled into C57BL/6 mice. The mice were then examined for biomarkers of inflammation and injury, as well as examined histologically for development of pulmonary disease as a function of dose and time. Biomarkers for pulmonary inflammation included cytokines, mediators and the presence of inflammatory cells (IL-1β, IL-18, IL-33, cathepsin B and neutrophils) and markers of injury (albumin and lactate dehydrogenase). The results show that surface modification by the addition of the -COOH group to the MWCNT, significantly reduced the bioactivity and pathogenicity. The results of this study also suggest that in vivo pathogenicity of the BMWCNT and FMWCNT correlates with activation of the NLRP3 inflammasome in the lung.